Lithium-containing silicon-based dense ceramic of olivine type and method for the production thereof

CN119100772BActive Publication Date: 2026-11-03YULIN NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411309879.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2026-11-03
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare olivine-type lithium-silicon-based ceramics with a relative density greater than 95% without using hot pressing sintering, and their microwave dielectric properties are not ideal.

Method used

High-entropy lithium-containing silicon-based olivine ceramics were prepared by using a traditional high-temperature solid-state synthesis method, employing two or more metal cations to co-substitute In3+, and sintering in the range of 1050℃~1110℃ to produce dense ceramics with excellent microwave dielectric properties.

Benefits of technology

This study achieved the production of olivine-type lithium-silicon-based ceramics with high relative density and excellent microwave dielectric properties under low-temperature sintering conditions, while reducing the amount of In2O3 used and simplifying the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119100772B_ABST
    Figure CN119100772B_ABST
Patent Text Reader

Abstract

The application provides an olivine-type lithium-containing silicon-based dense ceramic and a preparation method thereof. 1‑x M x SiO4 (0.35≤x≤0.8), wherein M must contain Yb element and further comprises at least one of Zn, Ni, Ga, Y, Eu, Ho, Er and Tm, and the total of the subscripts of the elements in M is equal to the value of x. The application adopts a traditional solid-phase reaction sintering method, and the process is simple. Without additional sintering aids or hot-press sintering, the olivine-type lithium-containing silicon-based dense ceramic with excellent comprehensive microwave dielectric performance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electronic functional ceramics technology, specifically relating to a lithium-silicon-based dense ceramic with an olivine structure and its preparation method. Background Technology

[0002] With the promotion of 5G technology and the deployment of 6G technology, microwave communication technology will extend to the millimeter-wave band. Electronic components based on low-dielectric-constant microwave dielectric ceramics have the characteristics of fast signal transmission response and low dielectric loss at high frequencies, and are widely used in substrates, dielectric filters, dielectric resonators and other fields.

[0003] Olivine-type (chemical formula ABCO4) microwave dielectric ceramics are a class of ceramics with a dielectric constant (ε). r Microwave dielectric materials generally have low quality factors. Among them, magnesium olivine (Mg2SiO4) has an extremely high quality factor (Q×f value), but Mg2SiO4 and its modified series of silicon-based olivine ceramics have very high sintering temperatures (1300℃~1500℃), which is not conducive to the application of low-temperature co-firing technology. Germanium-based olivines such as CaMgGeO4, Ca2GeO4, Mg2GeO4, and NaYGeO4 have relatively lower sintering temperatures (1200℃~1450℃) compared to silicon-based olivines, but the raw material GeO2 is expensive, which is not conducive to large-scale production. LiMgPO4 and its modified series of phosphorus-based olivines are prone to moisture absorption and have a low temperature coefficient of resonant frequency (τ). f The negative values ​​are generally large (-60 to -90 ppm / ℃), requiring complex modification processes to meet practical needs.

[0004] Olivine-type LiInSiO4 microwave dielectric ceramics are a series of low-dielectric microwave dielectric ceramics with moderate sintering temperatures (1050℃~1150℃). For example, LiInSiO4 exhibits promising microwave dielectric properties at 1150℃. r =8.2, Q×f=12600GHz, τ f= -55ppm / ℃; however, due to its low density (relative density ≤91%), its Q×f value is relatively low. After adding sintering aids, the microstructure of the ceramic is effectively improved, the density is significantly increased, and the Q×f value can reach up to 22000GHz (J. Alloys Compd. 552 (2013) 83-87). In addition, lithium-containing silicon-based olivine LiYbSiO4 (Ceram. Int. 46 (2020) 19996–20003), LiHoSiO4 (Ceram. Int. 50 (2024) 31278-31286) and LiTmSiO4 (J. Mater. Sci. Mater. Electron. (2024) 35: 1468), which also have low dielectric constants, also have low sintering temperatures and small τ. f While their absolute values ​​are high, their Q×f values ​​are also somewhat lacking due to their less-than-ideal relative density (<95%) (maximum only 25276 GHz).

[0005] In fact, without any sintering aids or under non-hot-pressing sintering conditions, it is difficult to obtain a dense microstructure and relative density when preparing lithium-containing silicate ceramics using ordinary high-temperature solid-state reaction sintering methods. This is mainly due to the large difference in melting points between Li₂O and SiO₂, and the lower melting point of Li₂O. + It is easily volatilized at high temperatures, causing numerous pores to form in the ceramic microstructure, ultimately resulting in low density of the ceramic sample. Besides lithium-containing silicon-based olivine, other lithium-containing silicates such as LiGaSiO4 (Ceram.Int.50(2024)7758-7766) and Li(Zn) also exhibit this characteristic. 0.95 Co 0.05 ) 1.5 SiO4 (Ceram.Int.43(2017)7636-7640) and LiRe9(SiO4)6O2 (J.Am.Ceram.Soc.96(2013)1504–1511) also exhibit low Q×f values ​​due to their undesirable relative density (<95%).

[0006] High-entropy ceramics mainly refer to single-phase solid solution ceramics formed by four or more ceramic components. High-entropy ceramics exhibit high-entropy effects, lattice distortion effects, cocktail effects, and hysteretic diffusion effects, which give them advantages over traditional single-component ceramics, such as higher hardness, strength, wear resistance, thermal stability, and lower thermal conductivity. However, whether high-entropy ceramics necessarily achieve higher density is not yet clearly understood. Literature indicates that in a series of high-entropy ceramics with fluorite structures, (Hf... 0.25 Zr 0.25 Ce 0.25 (Y) 0.125 Ca 0.125 )O2-δ The relative density can reach 98.5%, but (Hf 0.2 Zr 0.2 Ce 0.2 (Y) 0.2 Yb 0.2 )O 2-δ Its relative density is only 93.7%, while (Hf) 0.25 Zr 0.25 Ce 0.25 (Yb) 0.125 Gd 0.125 )O 2-δ With (Hf) 0.2 Zr 0.2 Ce 0.2 (Yb) 0.2 Gd 0.2 )O 2-δ The relative densities are even lower, at 77.8% and 68.4% (J.Eur.Ceram.Soc.38(2018)3578-3584). In addition to the high-entropy oxide ceramics mentioned above, Gild also found that the relative densities of a series of high-entropy borate ceramics were all below 92.5% (Scientific Reports 6:37946(2016)).

[0007] Current research on olivine-type high-entropy LiASiO4 is limited, and as mentioned above, high-entropy ceramics do not necessarily have a higher relative density compared to single-principal-element ceramics. Obtaining olivine-type lithium-containing silicon-based ceramics with a relative density greater than 95% and excellent microwave dielectric properties is a challenging problem, and solving this problem will provide valuable reference for the densification of other lithium-containing silicates. Summary of the Invention

[0008] To address the aforementioned problems, the present invention aims to provide an olivine-type lithium-silicon-based dense ceramic and its preparation method. This invention primarily focuses on olivine-type LiInSiO4, using two or more metal cations to co-substitute In. 3+ Based on the basic idea, non-equimolar ratio components or equimolar ratio components are used to jointly occupy In. 3+ The proposed scheme utilizes high-entropy lithium-containing silicon-based olivine to prepare dense ceramics through a simple traditional high-temperature solid-state synthesis method without the need for hot-pressing sintering. This method also reduces the amount of expensive In2O3 required, ultimately yielding olivine-type lithium-containing silicon-based dense ceramics with excellent comprehensive microwave dielectric properties.

[0009] To overcome the shortcomings of the prior art, the technical solution of the present invention is as follows:

[0010] An olivine-type lithium-silicon-based dense ceramic, characterized in that the general chemical formula of the lithium-silicon-based dense ceramic is LiIn. 1-x M x SiO4 (0.35≤x≤0.8), wherein M must contain Yb and also includes at least one element selected from Zn, Ni, Ga, Y, Eu, Ho, Er, and Tm, and the sum of the subscripts of all elements in M ​​equals the value of x. The olivine-type lithium-silicon-based dense ceramic has a relative permittivity ε. r The frequency response time is 7.49–7.88, the quality factor Q×f is 15440–30770 GHz, and the temperature coefficient of resonant frequency τ is [not specified]. f The concentration is between -40.4 ppm / ℃ and -14.6 ppm / ℃. The olivine-type lithium-silicon-based dense ceramic is characterized in that the sintering temperature range of the lithium-silicon-based dense ceramic is between 1050℃ and 1110℃; when the chemical formula of the lithium-silicon-based dense ceramic is LiIn... 0.65 Yb 0.2 Ga 0.15 In the SiO4 phase, the ceramic contains a second phase In2O3 in addition to the main phase olivine; when the chemical formula of the lithium-containing silicon-based dense ceramic is Li(InYb)... 0.4 (GaEu) 0.1 In the SiO4 form, the ceramic contains two impurity phases besides the main phase olivine, one of which is In2O3; when the chemical formula of the lithium-silicon-based dense ceramic is LiIn 0.3 (GaYEuHoErYbTm) 0.1 In the SiO4 stage, the ceramic contains two impurity phases besides the main phase olivine, one of which is In2O3; when the chemical formula of the lithium-containing silicon-based dense ceramic is Li(InYb). 0.3 (GaEuHoTm) 0.1 In SiO4, the ceramic contains an impurity phase in addition to the main phase olivine.

[0011] The method for preparing the olivine-type lithium-silicon-based dense ceramic includes the following steps:

[0012] (1) Weigh Li2CO3, In2O3, SiO2 and the metal oxide of M according to the proportions of the general chemical formula, and mix them together to form a raw material mixture;

[0013] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0014] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0015] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0016] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0017] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1050℃~1110℃, and the target temperature is held for 5 hours. Then, cool it with the furnace to obtain olivine-type lithium silicon-based dense ceramic.

[0018] Preferably, the sintering process in step 6 is divided into two different heating rates: the heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour; then the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0019] Compared with the prior art, the advantages of the present invention are: the material provided by the present invention has a low dielectric constant (7.49-7.88), which can reduce signal delay time; a generally high quality factor (15440-30770 GHz), which can improve the selectivity of device operating frequency; and a smaller τ. f The value ensures the thermal stability of the device. The ceramic preparation process of this invention adopts the traditional high-temperature solid-state synthesis method, and the sintering temperature is below 1120℃. The process is simple and does not require the addition of additional sintering aids or hot pressing sintering to obtain olivine-type lithium-silicon-based dense ceramics with excellent comprehensive microwave dielectric properties. Attached Figure Description

[0020] Figure 1 LiIn is a lithium-containing silicon-based olivine-type compound. 1-x M x XRD pattern of SiO4 (0.35≤x≤0.8; where M must contain Yb and also includes at least one of Zn, Ni, Ga, Y, Eu, Ho, Er, Tm) ceramics;

[0021] Figure 2 LiIn 0.5 Yb 0.4 Ga 0.1 Microscopic morphology of SiO4 ceramics;

[0022] Figure 3 For Li(InYb) 0.3 (GaEuHoTm) 0.1 Microscopic morphology of SiO4 ceramics. Detailed Implementation

[0023] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0024] Example 1:

[0025] (1) According to the general chemical formula LiIn 0.2 Yb 0.7 Ga 0.1 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, and Ga2O3, which are weighed out and mixed together to form a raw material mixture.

[0026] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0027] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0028] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0029] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0030] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1110℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0031] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0032] Example 2:

[0033] (1) According to the general chemical formula LiIn 0.2 Yb 0.65 Ni 0.15 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, and NiO, which are weighed out and mixed together to form a raw material mixture.

[0034] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0035] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0036] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0037] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0038] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1100℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0039] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0040] Example 3

[0041] (1) According to the general chemical formula LiIn 0.2 Yb 0.65 Zn 0.15 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, and ZnO, which are weighed out and mixed together to form a raw material mixture.

[0042] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0043] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0044] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0045] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0046] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1050℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0047] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0048] Example 4

[0049] (1) According to the general chemical formula LiIn 0.5 Yb 0.4 Ga 0.1 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, and Ga2O3, which are weighed out and mixed together to form a raw material mixture.

[0050] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0051] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0052] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0053] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0054] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1100℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0055] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0056] Example 5

[0057] (1) According to the general chemical formula Li(InYb) 0.3 (GaEuHoTm) 0.1 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, Ga2O3, Eu2O3, Ho2O3, and Tm2O3, which are weighed out and mixed together to form a raw material mixture.

[0058] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0059] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0060] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0061] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0062] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1090℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0063] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0064] Example 6

[0065] (1) According to the general chemical formula LiIn 0.65 Yb 0.2 Ga 0.15 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, and Ga2O3, which are weighed out and mixed together to form a raw material mixture.

[0066] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0067] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0068] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0069] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0070] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1090℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0071] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0072] Example 7

[0073] (1) According to the general chemical formula Li(InYb) 0.4 (GaEu) 0.1 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, Ga2O3, and Eu2O3, which are weighed out and mixed together to form a raw material mixture.

[0074] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0075] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0076] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0077] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0078] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1110℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0079] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0080] Example 8

[0081] (1) According to the general chemical formula LiIn 0.3 (GaYEuHoErYbTm) 0.1 The SiO4 mixture consists of Li2CO3, In2O3, SiO2, Yb2O3, Ga2O3, Eu2O3, Y2O3, Ho2O3, Er2O3, and Tm2O3, which are weighed out and mixed together to form a raw material mixture.

[0082] (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder.

[0083] (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material;

[0084] (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder.

[0085] (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C.

[0086] (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1070℃, and the furnace is kept at the target temperature for 5 hours. Then, the furnace is cooled to obtain olivine-type lithium silicon-based dense ceramic.

[0087] In this specific embodiment, the sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

[0088] The ceramics obtained by sintering in Examples 1 to 8 were tested by XRD, and the results are shown in the appendix. Figure 1 As shown, the phases of these ceramics are all olivine-structured phases. Among them, LiIn... 0.65 Yb 0.2 Ga 0.15 In addition to the main phase olivine, SiO4 ceramics also contain secondary phases In₂O₃ and Li(InYb). 0.4 (GaEu) 0.1 In addition to the main phase olivine, SiO4 ceramics also contain two impurity phases, one of which is In₂O₃; LiIn 0.3 (GaYEuHoErYbTm) 0.1 In addition to the main phase olivine, SiO4 ceramics also contain two impurity phases, one of which is In₂O₃; Li(InYb) 0.3 (GaEuHoTm) 0.1 In addition to the main phase olivine, SiO4 ceramics also contain an impurity phase.

[0089] The apparent density of the ceramics obtained by sintering in Examples 1 to 8 was tested using the Archimedes' displacement method. The density was then refined using the corresponding XRD data for each ceramic, and the theoretical density was calculated based on the refined data. Finally, the relative density of the ceramics was calculated based on the apparent density and the theoretical density. The results are shown in Table 1. The ceramics of each example exhibited a high relative density. Besides the potential factor of multiple cations occupying the same lattice position, densification may also be related to the ceramic green body prepared by mixing powders of different particle sizes in a certain mass ratio after granulation and sieving during the preparation process. Furthermore, Table 1 provides the microwave dielectric properties of each specific example. Figure 1 The XRD results show that ceramic samples with impurity phases, or even multiple impurity phases, exhibit lower Q×f values, which may be related to the impurity phases.

[0090] Figure 2 LiIn in Example 40.5 Yb 0.4 Ga 0.1 Microscopic morphology images of SiO4 ceramics. The images show that traditional high-temperature solid-state synthesis methods can produce ceramics with varying grain sizes but clear grain boundaries and a compact, dense microstructure. From the relative density and microscopic morphology images, it can be inferred that when a certain molar ratio of In... 3+ Yb 3+ and Ga 3+ When two particles occupy the same lattice site, they can promote the densification of ceramics, which in turn helps to improve the Q×f value of ceramics.

[0091] Figure 3 Li(InYb) in Example 5 0.3 (GaEuHoTm) 0.1 Microscopic morphology images of SiO4 ceramics. The images also show that ceramics with compact grain distribution and relatively dense microstructure can be prepared using traditional high-temperature solid-state synthesis methods. From the relative density and microstructure images, it can be inferred that when a certain molar ratio of In... 3+ Yb 3+ Ga 3+ Eu 3+ Ho 3+ and Tm 3+ When grains occupy the same lattice position, the resulting high-entropy ceramic may experience slow grain growth at high temperatures due to hysteresis diffusion, which could promote ceramic densification. However, the presence of a small amount of impurity phases, such as Li(InYb), may also contribute to this. 0.3 (GaEuHoTm) 0.1 The Q×f value of SiO4 ceramics is not high enough.

[0092] Table 1

[0093]

[0094] The above description is a further detailed explanation of the present invention in conjunction with specific preferred embodiments. It should not be considered that the specific embodiments of the present invention are limited to this. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention, and all of these should be considered to fall within the scope of patent protection determined by the claims submitted by the present invention.

Claims

1. An olivine-type lithium-silicon-based dense ceramic, characterized in that, The general chemical formula of the lithium-containing silicon-based dense ceramic is LiIn. 1-x M x SiO4 (0.35≤x≤0.8), wherein M must contain the element Yb and also includes at least one element from Zn, Ni, Ga, Y, Eu, Ho, Er, and Tm, and the sum of the subscripts of all elements in M ​​is equal to the value of x.

2. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, The relative permittivity ε of the lithium-containing silicon-based dense ceramic r The GHz range is 7.49 to 7.88, and the quality factor Q×f is 15440 to 30770 GHz.

3. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, The resonant frequency temperature coefficient τ of the lithium-silicon-based dense ceramic f Between -40.4 ppm / ℃ and -14.6 ppm / ℃.

4. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, The sintering temperature range of the lithium-containing silicon-based dense ceramic is between 1050℃ and 1110℃.

5. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, When the number of elements M in the lithium-containing silicon-based dense ceramic is 2, and the chemical formula is LiIn 0.65 Yb 0.2 Ga 0.15 In the SiO4 phase, the ceramic contains a second phase In2O3 in addition to the main phase olivine.

6. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, When the number of elements M in the lithium-containing silicon-based dense ceramic is 3, and the chemical formula is Li(InYb) 0.4 (GaEu) 0.1 In the SiO4 phase, the ceramic contains two impurity phases in addition to the main phase olivine, one of which is In2O3.

7. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, When the number of elements M in the lithium-containing silicon-based dense ceramic is 7, and the chemical formula is LiIn 0.3 (GaYEuHoErYbTm) 0.1 In the SiO4 phase, the ceramic contains two impurity phases in addition to the main phase olivine, one of which is In2O3.

8. The lithium-containing silicon-based dense ceramic according to claim 1, characterized in that, When the number of elements M in the lithium-containing silicon-based dense ceramic is 5, and the chemical formula is Li(InYb) 0.3 (GaEuHoTm) 0.1 In SiO4, the ceramic contains an impurity phase in addition to the main phase olivine.

9. A method for preparing lithium-silicon-based dense ceramics as described in any one of claims 1-8, characterized in that, Includes the following steps: (1) Weigh Li2CO3, In2O3, SiO2 and the metal oxide of M according to the proportions of the general chemical formula, and mix them together to form a raw material mixture; (2) Place the raw material mixture from step 1 into a polytetrafluoroethylene ball mill jar, use zirconium dioxide balls and anhydrous ethanol as the ball milling media, and mill for 4 hours. Then dry to obtain the mixture powder. (3) The dried mixture powder is placed in a high-temperature furnace for pre-calcination, that is, the temperature is raised from room temperature to 900°C and held at this temperature for 3 hours before being cooled with the furnace to obtain the pre-calcined material; (4) The pre-burned material obtained in step 3 is ball-milled with zirconium dioxide balls and anhydrous ethanol as the ball-milling media for 6 hours, and then dried to obtain powder. (5) Add binder to the powder obtained after drying in step 4, then granulate and sieve. During the sieving process, place a bottom plate at the bottom, a 120-mesh standard sieve in the middle, and a 60-mesh standard sieve at the top. Take the powder that passes through the 60-mesh standard sieve and remains on the 120-mesh standard sieve as powder A, and take the powder that passes through the 120-mesh standard sieve and remains on the bottom plate as powder B. Then weigh powder A and powder B at a mass ratio of 3:1 and grind them evenly in an agate mortar. Then transfer them to a beaker containing anhydrous ethanol, and place the beaker in an ultrasonic cleaner for ultrasonic dispersion for 10 minutes. Dry to obtain powder C. (6) Place a portion of the C powder from step 5 into a mold, press it into a cylinder at 170 MPa and place it in a crucible. Then, pour another portion of the C powder into the crucible as a sintering powder, so that the sintering powder wraps around and covers the cylinder. Then, place the crucible into a high-temperature furnace for sintering. The target sintering temperature is 1050℃~1110℃, and the target temperature is held for 5 hours. Then, cool it with the furnace to obtain olivine-type lithium silicon-based dense ceramic.

10. The method for preparing lithium-containing silicon-based dense ceramics as described in claim 9, characterized in that, The sintering process in step 6 is divided into two different heating rates. The heating rate before 550°C is 1.5°C / min, and the temperature is held at 550°C for 1 hour. Then, the temperature is increased from 550°C to the target temperature, and the heating rate in this heating range is 3°C / min.

Citation Information

Patent Citations

  • Application of LiInSiO4 as low-loss stable-temperature microwave dielectric ceramic

    CN105967667A

  • Silicon-based temperature-stable type microwave dielectric ceramic material and preparation method thereof

    CN111470864A

  • High-entropy ceramic with olivine structure and preparation method thereof

    CN117902892A